Control estadístico de calidad en los procesos de fermentación y destilación de la producción de Ron Cartavio en la empresa “Destilerías Unidas” SAC. período mayo - junio 2012 - Castañeda Santisteban, Erika Jaqueline (2012)
This report deals with the study of Statistical Quality Control of the Molasses Brix, Brix fermented,% ART or Sugar and Alcoholic (Wort) in the fermentation process, in the same way to the alcohol content and acidity variables Acetic acid in the distillation process of Cartavio rum production in the Company "United Breweries" SAC period from May to June 2012. The main objective is to determine whether the Molasses Brix, Brix fermented,% ATR or sugar and alcohol content (must) of the fermentation process is in statistical control, in the same way, the alcoholic and acetic acidity Process Distillation is under statistical control, corresponding to Cartavio rum manufacturing, using statistical methods, such as: Quality Control Charts and Process Capability. Data collection was carried out in sheets and control monitoring records G - F - 001 area designed for quality control of the company. To collect the sample elements used systematic sampling, using a sample size of 150 observations that were considered in 15 subsamples each of 10 observations. It was verified that the Brix of the molasses, fermented Brix, % ATR or Sugar and Alcoholic (Wort) in the fermentation process, the variables follow a normal distribution, likewise the variables in the fermentation process are correlated. For the distillation process, variables Alcoholic and Acetic Acid follow a normal distribution, but are not correlated. Therefore control charts applied multivariate generalized mean and variance for the variables for the fermentation process and applied univariate control charts of mean and standard deviation for each variable for the distillation process, we also determined the ability of by process capability index for each variable respectively of the fermentation and distillation processes. The fermentation and distillation processes are outside the control limits, so it is appropriate to make further steps to analyze the behavior of the processes and then take appropriate decisions